3D Diffraction Imaging of Linear Features and its Application to Seismic Monitoring - Alonaizi, Faisal Abdulkader; Pevzner, Roman; Bona, Andrej; Gurevich, Boris (EAGE, 2013)
Many subsurface features, such as faults, fractures, cracks, or fluid content terminations are defined by geological discontinuities. Seismic response from such features is encoded in diffractions. We develop an algorithm for imaging such discontinuities by detecting edge diffractions. The algorithm exploits phase-reversal phenomena of edge diffractions, and uses them as a criterion to separate diffractions from specular reflections. The performance of the method has been demonstrated on both synthetic and real 3D seismic data. The output image focuses the diffracted energy back to its origin, and shows high semblance values at the edge of the object. The method is applied on conventionally stacked data producing an image contains only diffraction events called (D-volume). We also reveal the potential of diffractions to image and track the changes of the CO2 plume using time-lapse analysis and detect any possible CO2 seepage from its primary containment.